World English ( Teacher's book ) (Harcourt, Brace International, 1982)
This book present suggestions for teaching each of the various elements of world english dialogues, exercises, listening activities, pronunciation section and so on. The experience of many teachers has demonstrated that these methods will be successful for the kinds of material in world english